Wildlife education in higher education institutions, its importance and encountered problems - Akkuzu, Erol; Ünal, Sabri; Evcin, Özkan (Isparta University of Applied Sciences Faculty of Forestry, 2014)
Yaban hayatı eğitiminin yükseköğretim kurumlarında yer alması süreci Türkiye ve gelişmiş batı ülkelerinde farklılıklar arz etmektedir. Özellikle Türkiye'de yaban hayatı ile ilgili program ve bölümlerin açılması hususu son yıllara kadar gerekli ilgiyi görmemiştir. Türkiye'de yaban hayatı eğitimi üniversitelerde ön lisans, lisans ve lisansüstü düzeyde verilmektedir. Ön lisans düzeyinde “Av ve Yaban Hayatı” ve “Avcılık ve Yaban Hayatı” programları mevcut olup çeşitli üniversiteler bünyesinde sayıları gün geçtikçe artmaktadır. Lisans düzeyinde “Yaban Hayatı Ekolojisi ve Yönetimi” bölümleri çoğunlukla orman fakülteleri bünyesinde yer almaktadır. Aktüel olarak orman fakülteleri dışında açılan tek bölüm Uşak Üniversitesi Ziraat ve Doğa Bilimleri Fakültesi'nde yer almaktadır. Bu derlemede, yaban hayatı eğitiminin önemi, Türkiye ve özellikle gelişmiş batı ülkelerindeki tarihi süreç, yaban hayatının ekonomiye katkısı, yaban hayatı eğitimi alan mezunların iş olanakları, sorunlar ve çözüm önerileri üzerinde durulmuştur. Anahtar kelimeler: Yaban hayatı, Üniversiteler, Eğitim, Ekonomi

As an historical process, wildlife educations in higher learning institutions have some differences in Turkey compared to those of the developed western countries. Especially, opening of the wildlife programs and departments has not received the necessary attention until recent years in Turkey. Wildlife education is given as associate degree, undergraduate and postgraduate levels in the Universities of Turkey. The number of associate degree programmes, named as “Hunting and Wildlife”, is increasing day by day within various universities. Departments of Wildlife Ecology and Management are mostly located within the forestry faculties. Only in Usak University, "Department of Wildlife Ecology and Management" is placed in the Faculty of Agriculture and Natural Sciences. In this review, the importance of wildlife education, its historical process in both Turkey and especially in developed western countries, its contribution to the economy, job opportunities, encountered problems and solutions were discussed. Keywords: Wildlife, Universities, Education, Economy
Keywords: ekonomi; education; economy; wildlife; Yaban hayatı; Üniversiteler; Eğitim; Ekonomi; Wildlife; Universities; Education; Economy; Forestry; -; üniversiteler; SD1-669.5; yaban hayatı; eğitim; universities